Influence of magnetic field and wall slip conditions on steady flow between parallel flat wall and a long wavy wall with Soret effect - Muthuraj, R.; Srinivas, S. (Journal of Naval Architecture and Marine Engineering, 2010)
The steady MHD flow in the presence of temperature dependent heat source in a viscous incompressible fluid bounded by a parallel flat wall and a long wavy wall is studied with heat and mass transfer, taking into account the thermal-diffusion (Soret) effects, when the no-slip condition at the channel wall in no longer valid. An external uniform magnetic field and a uniform suction are applied perpendicular to the flat wall. The walls are kept at different but constant temperatures. The velocity, temperature and concentration field have been evaluated numerically for various values of the parameters entering the problem. The skin friction, rate of heat and mass transfer at the walls are obtained and discussed graphically. Keywords: Wavy wall; slip parameter; Sherwood number; suction parameter; Soret number DOI: 10.3329/jname.v6i2.3061